Tourism As Osmosis: The Role of Apology Diplomacy in Shaping Tourist Arrivals in The Philippines - Noel Yee Sinco (Journal of Asian Social Science Research, 2025)
Abstract This paper examines how apology diplomacy influences foreign tourist arrivals to the Philippines from 2008 to 2025, introducing an innovative framework that views tourism as osmotic. Using a descriptive interrupted Time-Series Analysis (ITSA) of the Department of Tourism Data, the study analyzes key crises such as the 2010 Hong Kong hostage crisis, 2012 Scarborough Shoal Standoff, 2013 Taiwan fishermen shooting incident, the Canadian Garbage Crisis, the Tubbataha Reef Incident and other crises mentioned. While South Korea becomes a neutral (control) variable to analyze the fact that even if having a similar garbage crisis like Canada`s, it has strong tourism relations with the Philippines. It determines how political crises like these affect tourism recovery. Findings show that prompt and sincere public apologies function as a valve that restores tourist flows and repairs damaged bilateral relations, while unapologetic or delayed responses prolong travel bans and negative perceptions. The research concludes that apology diplomacy is a vital soft power instrument, translating symbolic gestures into economic and reputational gains. The Department of Tourism is recommended to implement this tourism risk management mechanisms in case of these kinds of crisis and not only the previous health pandemics (COVID or SARS). This osmosis model of tourism bridges diplomacy, development, and nation branding in the post-crisis context.